Associations of blood lipids and LDL cholesterol lowering drug-targets with colorectal cancer risk: a Mendelian randomisation study - Chan, Wing Ching; Liu, Lili; Bouras, Emmanouil; Zuber, Verena; Wen, Wanqing; Long, Jirong; Gill, Dipender; Murphy, Neil; Gunter, Marc J.; Assimes, Themistocles L.; Bujanda, Luis; Gruber, Stephen B.; et al. (British journal of cancer, 2025)
Whether blood lipids are causally associated with colorectal cancer (CRC) risk remains unclear.
Veröffentlicht: 23 November 2024
Gesehen am 11.07.2025